2021
DOI: 10.1007/s10924-021-02356-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, Thermal and Microstructural Characteristic of 3D Printed Polylactide Composites with Natural Fibers: Wood, Bamboo and Cork

Abstract: In the study, polylactide-based (PLA) composites modified with natural particles (wood, bamboo, and cork) and with different levels of infilling (100%, 80%, and 60%) obtained by fused deposition modeling were tested. The effect of fiber type, infill level and crystallization rate on the mechanical properties were investigated by using tensile, flexural, and impact tests. The materials were subjected to mechanical tests carried out at 23 and 80 °C. Differential scanning calorimetry were employed to analyze crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 40 publications
(43 reference statements)
2
31
0
Order By: Relevance
“…As shown in (Figures 7(a)-7(c)), the increase in porosity of the composites brought on by insufficient interfacial bonding is what leads to the drop in characteristics. The outcomes match those of the PLA composite with natural fibers work as determined by SEM [49]. Yusoff et al [62] found that while the flexural strength of kenaf-coir/ PLA was lower than kenaf-bamboo-coir/PLA and bamboocoir/PLA, it had the highest flexural modulus, which was 70% higher than the other combinations, as the impurities in bamboo fiber caused fiber-matrix interfacial failure and decreased the stiffness of the composites [62].…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…As shown in (Figures 7(a)-7(c)), the increase in porosity of the composites brought on by insufficient interfacial bonding is what leads to the drop in characteristics. The outcomes match those of the PLA composite with natural fibers work as determined by SEM [49]. Yusoff et al [62] found that while the flexural strength of kenaf-coir/ PLA was lower than kenaf-bamboo-coir/PLA and bamboocoir/PLA, it had the highest flexural modulus, which was 70% higher than the other combinations, as the impurities in bamboo fiber caused fiber-matrix interfacial failure and decreased the stiffness of the composites [62].…”
mentioning
confidence: 62%
“…However, as shown by SEM in Figures 7(b) and 7(c), the condition of poor adhesion between the fiber and the matrix had led to a reduction in tensile characteristics. According to study made by Mazur et al, PLA composites made with natural particles (Wood, Bamboo, and Cork), inadequate fiber/matrix adhesion, and empty spaces in the material had a detrimental impact on the material's mechanical characteristics [49]. Pongtanayut et al discovered that the insertion of soft phase rubber reduced the tensile strength of PLA matrix, suppressing PLA crystallinity and resulting in decreased tensile strength [50].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They established accurate crystal structure and the measurements taken between 25 and 150 C. The merits of polylactide are higher stiffness to strength ratio, biocompatibility, processability, and also its hydrophobic nature. [12] Polylactide are extensively employed in fused deposition modeling (3D printing) technique and used for aerospace, food packaging, pharmaceutical and biomedical applications. [13,14] The need for a biodegradable alternative material for engineering structures has prompted researchers to look at the utilization of natural resources as a part of advanced materials with the objective of reducing the use of steel, plastics in different structures.…”
Section: Introductionmentioning
confidence: 99%
“…The merits of polylactide are higher stiffness to strength ratio, biocompatibility, processability, and also its hydrophobic nature. [ 12 ] Polylactide are extensively employed in fused deposition modeling (3D printing) technique and used for aerospace, food packaging, pharmaceutical and biomedical applications. [ 13,14 ]…”
Section: Introductionmentioning
confidence: 99%